Beyond the Senses: How Self-Directed Speech and Word Meaning Structure Impact Executive Functioning and Theory of Mind in Individuals With Hearing and Language Problems - Camminga, Thomas F.; Hermans, Daan; Segers, Eliane; Vissers, Constance T. W. M. (Frontiers in Psychology, 2021)
Many individuals with hearing and language problems, including those with developmental language disorder (DLD) and individuals who are deaf or hard of hearing (D/HH), have behavioral problems that can be partly associated with their executive functions (EF) and theory of mind (ToM). The difficulties of both groups in EF and ToM may in turn be related to self-directed speech (i.e., overt or covert speech that is directed at the self). Self-directed speech is thought to allow for the construction of non-sensory representations (i.e., representations that do not coincide with direct observation). Based on non-sensory representations, individuals can overcome the limits set upon them by the senses. This ability is constrained by the development of word meaning structure (i.e., the way words are understood). We argue that the greater ability to construct non-sensory representations may result in more enhanced forms of EF and ToM. We conclude that difficulties in EF, ToM and social-emotional functioning in those with hearing and language problems may be accounted for in terms of word meaning impairments. We propose that word meaning structure and self-directed speech should be considered in assigning EF and ToM treatments to individuals with DLD and those that are D/HH.